Faktor-Faktor yang Memotivasi Mahasiswa Uniss untuk Menjadi Wirausaha - Setyawan, Suprihono; Ridwan, Ridwan (Jurnal Bingkai Ekonomi (JBE), 2021)
This study aims to analyze and examine the factors that influence UNISS Students’ interest in becoming entrepreneurs. This studi explores the analytical approaches used in mixed methods qualitative and quantitative with the number of respondents as many as 200 students of Selamat Sri University who have taken entrepreneurship courses. The 200 respondents who filled out forms in answering questionnaires just 144 students. The results showed that partially the Human Resource Factor was influence students' interest in becoming entrepreneurs (5.3%), then other Factors Capital was influenced 7.4%. The result showed that Students’ Motivation was influenced 6%. While Marketing factor was influenced 4%. And laast factor was Training influnced 5% student in becoming entrepreneurs. Simultaneously, the factors studied provided an explanation as showed by Coeficient determination number (17,4%), while other factors that are not studied are 82.6%.